Extensions 1→N→G→Q→1 with N=C22×C6 and Q=C3×S3

Direct product G=N×Q with N=C22×C6 and Q=C3×S3
dρLabelID
S3×C2×C62144S3xC2xC6^2432,772

Semidirect products G=N:Q with N=C22×C6 and Q=C3×S3
extensionφ:Q→Aut NdρLabelID
(C22×C6)⋊1(C3×S3) = C3×C6×S4φ: C3×S3/C3S3 ⊆ Aut C22×C654(C2^2xC6):1(C3xS3)432,760
(C22×C6)⋊2(C3×S3) = C6×C3⋊S4φ: C3×S3/C3S3 ⊆ Aut C22×C6366(C2^2xC6):2(C3xS3)432,761
(C22×C6)⋊3(C3×S3) = C2×A4×C3⋊S3φ: C3×S3/C3C6 ⊆ Aut C22×C654(C2^2xC6):3(C3xS3)432,764
(C22×C6)⋊4(C3×S3) = S3×C6×A4φ: C3×S3/S3C3 ⊆ Aut C22×C6366(C2^2xC6):4(C3xS3)432,763
(C22×C6)⋊5(C3×S3) = C3×C6×C3⋊D4φ: C3×S3/C32C2 ⊆ Aut C22×C672(C2^2xC6):5(C3xS3)432,709
(C22×C6)⋊6(C3×S3) = C6×C327D4φ: C3×S3/C32C2 ⊆ Aut C22×C672(C2^2xC6):6(C3xS3)432,719
(C22×C6)⋊7(C3×S3) = C3⋊S3×C22×C6φ: C3×S3/C32C2 ⊆ Aut C22×C6144(C2^2xC6):7(C3xS3)432,773

Non-split extensions G=N.Q with N=C22×C6 and Q=C3×S3
extensionφ:Q→Aut NdρLabelID
(C22×C6).1(C3×S3) = C9×A4⋊C4φ: C3×S3/C3S3 ⊆ Aut C22×C61083(C2^2xC6).1(C3xS3)432,242
(C22×C6).2(C3×S3) = C18×S4φ: C3×S3/C3S3 ⊆ Aut C22×C6543(C2^2xC6).2(C3xS3)432,532
(C22×C6).3(C3×S3) = C32×A4⋊C4φ: C3×S3/C3S3 ⊆ Aut C22×C6108(C2^2xC6).3(C3xS3)432,615
(C22×C6).4(C3×S3) = C62.Dic3φ: C3×S3/C3S3 ⊆ Aut C22×C6366-(C2^2xC6).4(C3xS3)432,249
(C22×C6).5(C3×S3) = C3×C6.S4φ: C3×S3/C3S3 ⊆ Aut C22×C6366(C2^2xC6).5(C3xS3)432,250
(C22×C6).6(C3×S3) = C625Dic3φ: C3×S3/C3S3 ⊆ Aut C22×C6366-(C2^2xC6).6(C3xS3)432,251
(C22×C6).7(C3×S3) = C2×C32.S4φ: C3×S3/C3S3 ⊆ Aut C22×C6186+(C2^2xC6).7(C3xS3)432,533
(C22×C6).8(C3×S3) = C6×C3.S4φ: C3×S3/C3S3 ⊆ Aut C22×C6366(C2^2xC6).8(C3xS3)432,534
(C22×C6).9(C3×S3) = C2×C62⋊S3φ: C3×S3/C3S3 ⊆ Aut C22×C6186+(C2^2xC6).9(C3xS3)432,535
(C22×C6).10(C3×S3) = C3×C6.7S4φ: C3×S3/C3S3 ⊆ Aut C22×C6366(C2^2xC6).10(C3xS3)432,618
(C22×C6).11(C3×S3) = Dic9⋊A4φ: C3×S3/C3C6 ⊆ Aut C22×C61086-(C2^2xC6).11(C3xS3)432,265
(C22×C6).12(C3×S3) = A4×Dic9φ: C3×S3/C3C6 ⊆ Aut C22×C61086-(C2^2xC6).12(C3xS3)432,266
(C22×C6).13(C3×S3) = C624C12φ: C3×S3/C3C6 ⊆ Aut C22×C6366-(C2^2xC6).13(C3xS3)432,272
(C22×C6).14(C3×S3) = C2×D9⋊A4φ: C3×S3/C3C6 ⊆ Aut C22×C6546+(C2^2xC6).14(C3xS3)432,539
(C22×C6).15(C3×S3) = C2×A4×D9φ: C3×S3/C3C6 ⊆ Aut C22×C6546+(C2^2xC6).15(C3xS3)432,540
(C22×C6).16(C3×S3) = C2×C62⋊C6φ: C3×S3/C3C6 ⊆ Aut C22×C6186+(C2^2xC6).16(C3xS3)432,542
(C22×C6).17(C3×S3) = A4×C3⋊Dic3φ: C3×S3/C3C6 ⊆ Aut C22×C6108(C2^2xC6).17(C3xS3)432,627
(C22×C6).18(C3×S3) = Dic3×C3.A4φ: C3×S3/S3C3 ⊆ Aut C22×C6366(C2^2xC6).18(C3xS3)432,271
(C22×C6).19(C3×S3) = C2×S3×C3.A4φ: C3×S3/S3C3 ⊆ Aut C22×C6366(C2^2xC6).19(C3xS3)432,541
(C22×C6).20(C3×S3) = C3×Dic3×A4φ: C3×S3/S3C3 ⊆ Aut C22×C6366(C2^2xC6).20(C3xS3)432,624
(C22×C6).21(C3×S3) = C9×C6.D4φ: C3×S3/C32C2 ⊆ Aut C22×C672(C2^2xC6).21(C3xS3)432,165
(C22×C6).22(C3×S3) = C18×C3⋊D4φ: C3×S3/C32C2 ⊆ Aut C22×C672(C2^2xC6).22(C3xS3)432,375
(C22×C6).23(C3×S3) = C32×C6.D4φ: C3×S3/C32C2 ⊆ Aut C22×C672(C2^2xC6).23(C3xS3)432,479
(C22×C6).24(C3×S3) = C3×C18.D4φ: C3×S3/C32C2 ⊆ Aut C22×C672(C2^2xC6).24(C3xS3)432,164
(C22×C6).25(C3×S3) = C623C12φ: C3×S3/C32C2 ⊆ Aut C22×C672(C2^2xC6).25(C3xS3)432,166
(C22×C6).26(C3×S3) = C62.27D6φ: C3×S3/C32C2 ⊆ Aut C22×C672(C2^2xC6).26(C3xS3)432,167
(C22×C6).27(C3×S3) = C2×C6×Dic9φ: C3×S3/C32C2 ⊆ Aut C22×C6144(C2^2xC6).27(C3xS3)432,372
(C22×C6).28(C3×S3) = C6×C9⋊D4φ: C3×S3/C32C2 ⊆ Aut C22×C672(C2^2xC6).28(C3xS3)432,374
(C22×C6).29(C3×S3) = C22×C32⋊C12φ: C3×S3/C32C2 ⊆ Aut C22×C6144(C2^2xC6).29(C3xS3)432,376
(C22×C6).30(C3×S3) = C2×He36D4φ: C3×S3/C32C2 ⊆ Aut C22×C672(C2^2xC6).30(C3xS3)432,377
(C22×C6).31(C3×S3) = C22×C9⋊C12φ: C3×S3/C32C2 ⊆ Aut C22×C6144(C2^2xC6).31(C3xS3)432,378
(C22×C6).32(C3×S3) = C2×Dic9⋊C6φ: C3×S3/C32C2 ⊆ Aut C22×C672(C2^2xC6).32(C3xS3)432,379
(C22×C6).33(C3×S3) = C3×C625C4φ: C3×S3/C32C2 ⊆ Aut C22×C672(C2^2xC6).33(C3xS3)432,495
(C22×C6).34(C3×S3) = D9×C22×C6φ: C3×S3/C32C2 ⊆ Aut C22×C6144(C2^2xC6).34(C3xS3)432,556
(C22×C6).35(C3×S3) = C23×C32⋊C6φ: C3×S3/C32C2 ⊆ Aut C22×C672(C2^2xC6).35(C3xS3)432,558
(C22×C6).36(C3×S3) = C23×C9⋊C6φ: C3×S3/C32C2 ⊆ Aut C22×C672(C2^2xC6).36(C3xS3)432,559
(C22×C6).37(C3×S3) = C2×C6×C3⋊Dic3φ: C3×S3/C32C2 ⊆ Aut C22×C6144(C2^2xC6).37(C3xS3)432,718
(C22×C6).38(C3×S3) = Dic3×C2×C18central extension (φ=1)144(C2^2xC6).38(C3xS3)432,373
(C22×C6).39(C3×S3) = S3×C22×C18central extension (φ=1)144(C2^2xC6).39(C3xS3)432,557
(C22×C6).40(C3×S3) = Dic3×C62central extension (φ=1)144(C2^2xC6).40(C3xS3)432,708

׿
×
𝔽